Traductionstranspositions: Représentations institutionnelles des Premiers Peuples du Canada - Lehmann, Florence (University of Ottawa (Canada), 2007)
To better understand the relationship to Otherness, postcolonial translation theorists have examined cultures that are far away in space or time. This dissertation takes an alternative approach by examining a contemporary, nearby Other, that is Native People who have been dominated over in a system that has "translated" them. This study analyzes a set of institutional representations of Canada's First Peoples. Its goal is to shed light on how these representations create a frame of reference that impacts public discourse about these people. Particular attention is paid to movements of consolidation , displacement, or subversion exercised within these frameworks. The review starts by recalling the historical conditions governing the first representations of Native People. It continues by analyzing the representations produced among the spheres of greatest influence: the legal, educational, museological, and linguistic institutions. How do the earliest colonial representations continue to filter through in present-day legal texts? How to educate tomorrow's decision makers about historical and current Native realities? How do museums construct the population's views of these realities? What is the status of Native languages against that of the two "official" languages of colonization? What support do Native languages receive, to allow them to assume their role in education and the development of Native identities, or for defining what is modern? These are the questions that each chapter explores and answers. The creation of the Dominion of Canada put the last touch to the definition of "Indians" as persons. Henceforth, power relations between First Peoples and colonizing forces became asymmetrical, and Canadian institutions got considerable powers of influence, not only over representations of the Native Other, but also over the production and reproduction of these representations. It is important that the subject, who reads and interprets Otherness through the symbolic representations that impact his/her frame of reference, be conscious of the predominance, in public discourse, of representations projected by institutions. This dissertation has attempted to uncover the competing power relations that are at work in representing Native People, while focusing on the position of people who represent, and on the position of those who are represented. This has led us to foreground areas of possible intervention favouring the recognition of Native people in Canada.
Keywords: Canadian Studies.; Speech Communication.; Native American Studies.